Detailed Analysis of Zebrafish Larval Behaviour in the Light Dark Challenge Assay Shows That Diel Hatching Time Determines Individual Variation - Rock, Sebastian; Rodenburg, Frans; Schaaf, Marcel J. M.; Tudorache, Christian (Frontiers in Physiology, 2022)
Research on stress coping style, i.e. the response of an organism to adverse conditions, which is constant over time and context, gained momentum in recent years, to better understand behavioural patterns in animal welfare. However, knowledge about the ontogeny of stress coping style is still limited. Here, we performed a detailed analysis of the light dark challenge behavioural assay in zebrafish larvae, where after acclimation in ambient light sudden alternating dark and light phases elicit an anxiety-like response. A principal component analysis on parameters related to locomotion (distance moved, swimming velocity, acceleration, mobility) and directionality (angular velocity, meandering of swimming path) revealed independence between the parameters determined in the light and the dark phases of the assay, indicating unrelated generalised behaviors per phase. However, high collinearity was observed between behavioral parameters within the same phase, indicating a robust response to the stimulus within behavioural phenotypes. Subsequently, this assay was used to determine the correlation between individual hatching time and the behavioral phenotype. The results show that fish that had hatched during daytime have a stronger behavioral response to the dark phase at 5 days post fertilization in locomotion related parameters and a weaker response in directionality related parameters, than fish that had hatched during nighttime. These results show that behavioural responses to the light dark challenge assay are robust and can be generalized for the light and the dark phase, and that diel hatching time may determine the behavioural phenotype of an individual.